TEACHING VOCABULARY USING THE UNISONO SINGING METHOD TO STUDENTS AT MTS HIFZHIL QUR’AN ISLAMIC CENTER FOUNDATION NORTH SUMATRA - Rafiza, Siti Nur; Lubis, Zulfahmi (Abjadia : International Journal of Education, 2024)
The unisono singing method is used in learning vocabulary to aid students in understanding new vocabulary by using rhythm and melody in music as reminders. This research aims to analyze the learning process and evaluation of learning at MTs Hifzhil Qur'an Islamic Center Foundation of North Sumatra by applying the unisono singing method with Arabic teachers. The research employs field research with a descriptive qualitative approach. It is very useful for delving deeper into the phenomenon under study, but it requires special attention to address subjectivity limitations and resource efficiency. Data collection techniques comprise observation, interviews, documentation. Data analysis involves collecting data through interviews, observation, and documentation, then reducing it through selection, after reduction, the data is presented in narrative text and tables, verification and conclusions are drawn through triangulation techniques. The analysis tool used is manual coding. Data validity is through data triangulation. The research results indicate that learning vocabulary using the unisono singing method is highly effective. Based on the learning outcomes of Class IX-5 students, they showcased an improvement before and after implementing the singing method. The mid-semester average score was 76, while the final-semester average score was 88.2. It was concluded that learning vocabulary with the unisono singing method was highly beneficial. This method serves as an effective and enjoyable tool in the Arabic language learning process as it offers practical advantages like enhancing pronunciation, vocabulary retention, learning motivation. Consequently, it can contribute to the advancement of Arabic language teaching methods in the field of education.